A preliminary inventory of biodiversity and benthic habitats of “Plane” Island (Paloma) in Oran Bay, north western Algeria, (western Mediterranean) - Hussein, K.B.; Talet, L.B. (Journal of the Black Sea / Mediterranean Environment, 2019)
This study aimed to create an inventory of the prominent species in “Plane” Island on the Algerian coast of the Mediterranean Sea for the conservation interest and to classify rocky benthic habitats. The study was carried out at eight stations by 27 dives between the surface and 34 m depth from 2014 to 2015. In total, 201 taxa were listed, of which 30% consists of macroalgae, 1% phanerogams, 52% macroinvertebrates and 17% fish. The biotope was characterized by the presence of 6 biocenosis of hard rock (19 associations and 9 facies). The bioconcretions were represented by red and yellow gorgonians and other sessile macrofauna that embellishes the coralligenous habitat. The macrobenthos were marked by the presence of several species. Exotic and sometimes invasive species were also present, such as Caulerpa racemosa var. cylindracea, Codium fragile, Asparagopsis armata, Asparagopsis taxiformis and Oculina patagonica. “Plane” Island represents a space with multiple stakes and uses, which requires a thorough study, valorization and a rational and durable exploitation in order to preserve its major assets. The study will provide support for the management of coastal ecosystems, such as those in “Plane” Island, aiming to create a marine protected area and the strengthening of fisheries regulations, as a veritable hot spot of biodiversity along the Algerian coasts